Author’s dictionary: categorial specifics and theoretical-applied significance (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article covers the problematics of author’s lexicography. It researches the basic notions of the stated linguistic line, defines the role of author’s dictionary in forming common language standards, and presents arguments for perspectivity of literary text lexicographic parameterization.
Keywords: lexicography; author’s dictionary; parameterization; literary text